IMPROVEMENT REFRACTORY QUALITY OF ALUMINA SILICATE FOR BRASS SMELTING WITH INFILTRATION TECHNIQUE - Ferli S. Irwansyah; Juliandri Juliandri; Iwan Hastiawan; Soewanto Rahardjo; Rifki Septawendar (Jurnal Zeolit Indonesia, 2010)
Requirement of refractory materials for manufacturing industry and metal smelting is increasing along technology development. Brass smelting needs a larger size ceramic crucible which is known by the name "kowi". Therefore, it needed a refractory material from local raw materials are higher quality, which has a low porosity, high density, and high mechanical strength. In this study was conducted increasing refractory quality of alumina silicate as a material for manufacturing a brass smelting kowi by infiltration technique. The raw materials such as kaolin, alumina, and magnesium oxide that has been determinate composition were brooded, printed, half-baked burned, infiltrated with a various concentrations, and then burned again, physical and chemical characteristic testing, and also used a Scanning Electron Microscope (SEM) to show morphology of refractory alumina silicate that have been infiltrated. The result showed that refractory alumina silicate was increase the qualities with porosity value of 11,36%, density value of 2,34 kg/m3, water absorbent of 4,85%, and mechanical strength of 129,072 kg/cm2 which can be used as "kowi" material for brass smelting industry.